Green supply chain management, risk-taking, and corporate value—Dual regulation effect based on technological innovation capability and supply chain concentration - Zhang, Lingfu; Dou, Yongfang; Wang, Hailing (Frontiers in Environmental Science, 2023)
With the promotion of carbon-peak and carbon-neutral strategies and the increase in green awareness, green development is gradually gaining attention, and the green supply chain management (GSCM) derived from traditional supply chain management is gradually becoming a path to promote green development. At the same time, enterprise, as an important source of pollution, how to consider social responsibility, such as environmental protection, in the process of ensuring efficiency improvement has become an important issue. To study the impact of GSCM on enterprise value and its path of action, this paper examines the impact of GSCM on enterprise value, explores the moderating effect of the risk-taking level, and further analyzes the dual moderating effect played by technological innovation capability and supply chain concentration. Based on the micro data of 131 Chinese listed enterprises from 2014 to 2021, a panel-regression model is used to illustrate how GSCM affects enterprise value, and the results show that: (1) GSCM can promote enterprise value; (2) the level of risk-taking strengthens the promoting effect of GSCM on enterprise value enhancement; and (3) the technological innovation capability negatively regulates the moderating effect of risk-taking, while the supply chain concentration positively regulates the moderating effect of risk-taking. The research results of this paper enrich the path of the effect of implementing of GSCM on enterprise value enhancement, i.e. the process of GSCM to enhance enterprise value is regulated by the level of enterprise risk-taking, while technological innovation capability and supply chain concentration will also regulate the level of enterprise risk-taking and thus promote enterprise value enhancement. This research not only extends the research perspective and enriches the existing research, but also provides a theoretical basis for enterprises to implement GSCM to promote value enhancement and improve the level of GSCM implementation and the green development of enterprises.